HEGEMONIC MASCULINITY IN ARCHETYPAL AFRICAN NOVELS - Amjad Alsyouf (Universitas Negeri Yogyakarta, 2018)
The study attempts to examine the concept of hegemonic masculinity in Tayeb Salih's Season of Migration to the North (1966) and Chinua Achebe’s Things Fall Apart (1958). To achieve that it deals with two concerns. First, it tackles the process of development of masculinity attempting to identify hegemonic masculinity among other stages within this process. Secondly, it investigates hegemonic masculinity as a concept occasionally occurs in popular African fiction with emphasis placed on its presence in Salih's Season of Migration to the North and Achebe’s Things Fall Apart. The research concludes with a recommendation to focus more research efforts on literature that deals with hypermasculinity, the stage succeeding hegemonic masculinity, as it needs immediate consideration due to its critical impact on contemporary world and audience.HEGEMONI MASKULINITAS DALAM NOVEL-NOVEL ARCHETYPAL AFRICANPenelitian yang bertujuan untuk mengkaji konsep mengenai hegemoni maskulinitas di Tayeb Salih’s Season of Migration to The North (1996) dan Chinua Achebe’s Things Fall Apart (1958) ini berfokus pada dua hal. Pertama, mengkaji proses perkembangan maskulinitas untuk mengidentifikasi hegemoni maskulinitas. Kedua, menginvestigasi hegemoni maskulinitas sebagai sebuah konsep yang selalu muncul dalam karya-karya fiksi afrika dengan penekanan pada Salih’s Season of Migration to The North and Achebe’s Things Fall Apart. Penelitian ini memberikan simpulan dan rekomendasi pada fokus penelitian selanjutnya yang berkaitan dengan hipermaskulinitas, seperti suksesnya hegemoni maskulinitas yang perlu dipertimbangkan penelitiannya karena dampak yang kritis dari dunia dan audiens saat ini.